Antimicrobial Activities of Bacteria Associated with the Brown Alga Padina pavonica - Ismail, Amel; Ktari, Leila; Ahmed, Mehboob; Bolhuis, Henk; Boudabbous, Abdellatif; Stal, Lucas J.; Cretoiu, Mariana Silvia; El Bour, Monia (Frontiers in Microbiology, 2016)
Macroalgae belonging to the genus Padina are known to produce antibacterial compounds that may inhibit growth of human- and animal pathogens. Hitherto, it was unclear whether this antibacterial activity is produced by the macroalga itself or by secondary metabolite producing epiphytic bacteria. Here we report antibacterial activities of epiphytic bacteria isolated from Padina pavonica (Peacocks tail) located on northern coast of Tunisia. Eighteen isolates were obtained in pure culture and tested for antimicrobial activities. Based on the 16S rRNA gene sequences the isolates were closely related to Proteobacteria (12 isolates; 2 Alpha- and 10 Gammaproteobacteria), Firmicutes (4 isolates) and Actinobacteria (2 isolates). The antimicrobial activity was assessed as inhibition of growth of twelve species of pathogenic bacteria (Aeromonas salmonicida, A. hydrophila, Enterobacter xiangfangensis, Enterococcus faecium, Escherichia coli, Micrococcus sp., Salmonella typhimurium, Staphylococcus aureus, Streptococcus sp., Vibrio alginoliticus, V. proteolyticus, V. vulnificus) and one pathogenic yeast (Candida albicans). Among the Firmicutes, isolate P8, which is closely related to Bacillus pumilus, displayed the largest spectrum of growth inhibition of the pathogenic bacteria tested. The results emphasize the potential use of P. pavonica associated antagonistic bacteria as producers of novel antibacterial compounds.